Integrasi Fuel Flow Control dan Combustion Air Flow Control pada Otomasi Kendali Tekanan Steam di Boiler - Ahmad Mahfud (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
Boiler is the main equipment in the mills. Boiler performance in generating steam greatly affect the performance of other work stations. Variability of performance variability Boiler major impact on the achievement of each work station. Steam pressure fluctuates, causing unstable processing quality. Some boiler using the system continues feeding, which will feed the fuel into the combustion chamber continuously even though the pressure has reached the set point, resulting in wasted fuel and water. Based on the data obtained, the system will generate steam boiler pressure fluctuating and less stable. Integration Fuel Combustion Air Flow Control and Flow Control is used to adjust the feed rate of fuel and air into the combustion chamber. Combustion effectiveness is emphasized in this integration, so that one of the parameters that can be seen visually is a perfect combustion conditions different smoke by burning less than perfect. Set Point which is a reference steam capacity is determined in this study amounted to 18.3 tons of steam / hour for a plant with a capacity of 30 tons / hour, by setting the Fuel Flow Control at 69% and Combustion Air Flow Control by 70%. Achievement vapor pressure generated by the integration of feeding fuel and air feed into the combustion chamber, resulting in vapor pressure are relatively stable at 20 bar in boilers and turbines, as well as the pressure of 3.2 bar in BPV.